Quantification of Tolerance Thresholds of Ramlik (Ziziphus nummularia L.) Seed Germination to Salinity Stresses at Different Temperatures - Fatemeh Primoradi; Abdolmahdi Bakhshandeh; Seyed Amir Moosavi; Mohammad Hossain Gharineh; Ali Moshatati (علوم و فناوری بذر ایران, 2022)
In order to investigate the combined effects of temperature and salinity stress on seed germination properties of ziziphus (Ramlik), a factorial experiment conducted at seed technology laboratory of Agricultural Sciences and Natural Resources University of Khuzestan in 2019. The experiment was arranged as complete block design with three raplications. First factor was salinity (0, 50, 100, 150, 200, 250 and 300 mM) and second factor was temperature (5, 10, 15, 20, 25, 30, 35 and 40 oC). Results of the experiment revealed that there was no seed germination in 5 oC, 10 oC at all salinity treatments. Seed germination and seedling growth were declined at all temperature treatments bythe increase in salinity concentrations. Salinity tolerance threshold of Ramlik at 25 OC was 173 mM but as temperature increased to 35 oC, it declined to 150 mM. The highest seed germination properties of Ramlik were observed at 25 oC. An increase in salinity led to a lower seed germination rate. As Ramlik seeds were capable to complete their germination at